Call to action regarding the vascular-bipolar link: A report from the Vascular Task Force of the International Society for Bipolar Disorders - Goldstein, Benjamin I; Baune, Bernhard T; Bond, David J; Chen, Pao-Huan; Eyler, Lisa; Fagiolini, Andrea; Gomes, Fabiano; Hajek, Tomas; Hatch, Jessica; McElroy, Susan L; McIntyre, Roger S; Prieto, Miguel; et al. (Bipolar disorders, 2020)
OBJECTIVES: The association of bipolar disorder with early and excessive cardiovascular disease was identified over a century ago. Nonetheless, the vascular-bipolar link remains underrecognized, particularly with regard to how this link can contribute to our understanding of pathogenesis and treatment. METHODS: An international group of experts completed a selective review of the literature, distilling core themes, identifying limitations and gaps in the literature, and highlighting future directions to bridge these gaps. RESULTS: The association between bipolar disorder and vascular disease is large in magnitude, consistent across studies, and independent of confounding variables where assessed. The vascular-bipolar link is multifactorial and is difficult to study given the latency between the onset of bipolar disorder, often in adolescence or early adulthood, and subsequent vascular disease, which usually occurs decades later. As a result, studies have often focused on risk factors for vascular disease or intermediate phenotypes, such as structural and functional vascular imaging measures. There is interest in identifying the most relevant mediators of this relationship, including lifestyle (eg, smoking, diet, exercise), medications, and systemic biological mediators (eg, inflammation). Nonetheless, there is a paucity of treatment studies that deliberately engage these mediators, and thus far no treatment studies have focused on engaging vascular imaging targets. CONCLUSIONS: Further research focused on the vascular-bipolar link holds promise for gleaning insights regarding the underlying causes of bipolar disorder, identifying novel treatment approaches, and mitigating disparities in cardiovascular outcomes for people with bipolar disorder.
Keywords: Adolescent; bipolar disorder; kouření; Adult; kardiovaskulární nemoci; Advisory Committees; dospělí; Humans; Cardiovascular Diseases; Bipolar Disorder; lidé; Risk Factors; atherosclerosis; rizikové faktory; poradní výbory; Smoking; mladiství; cardiovascular disease; stroke; prevention; vascular; bipolární porucha